Pengaruh Kompetensi Dosen Akuntansi, Metode Mengajar Dosen Akuntansi, Dan Kecerdasan Intelektual Mahasiswa Akuntansi Terhadap Tingkat Pemahaman Akuntansi - Putu Angelia Marheny; I Wayan Sudiana; Anak Agung Ketut Agus Suardika (UNHI Press, 2022)
The level of student accounting understanding must be considered to create quality accounting students. This study aims to determine the effect of the competence of accounting lecturers, teaching methods of accounting lecturers, and intellectual intelligence of accounting students on the level of accounting understanding of students in the accounting study program at the Hindu University of Indonesia. All students of the accounting study program at the Hindu University of Indonesia were the population, while the object of research (sample) were 7th semester students who had already received a full accounting course, as many as 225 people. The sampling technique used was purposive sampling method. The data were tested using validity test, reliability test, multicollinearity test, heteroscedasticity test, multiple regression analysis, hypothesis testing and coefficient of determination. The results showed that the variables of accounting lecturer competence, accounting lecturer teaching methods, and accounting students' intellectual intelligence had a positive and significant effect on the level of accounting understanding of students.